2020
DOI: 10.1001/jamapediatrics.2019.6083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose vs Standard-Dose Vitamin D Supplementation in Pregnancy on Bone Mineralization in Offspring Until Age 6 Years

Abstract: IMPORTANCE Studies suggest an association between maternal vitamin D status during pregnancy and offspring anthropometry and bone mineralization, but investigations are few and with mixed results.OBJECTIVE To investigate the effect of a high dose vs standard dose of vitamin D supplementation in pregnancy on anthropometric and bone outcomes until age 6 years in the offspring. DESIGN, SETTING, AND PARTICIPANTSA prespecified analysis of a double-blinded, randomized clinical trial in the Copenhagen Prospective Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 33 publications
(63 reference statements)
6
78
1
Order By: Relevance
“…Together with calcium, vitamin D helps protect This article is part of the Topical Collection on Photodermatology older adults from osteoporosis. There is strong, consistent evidence supporting the role of vitamin D in childhood bone health, although most studies have been done in a limited range of skin types, as exemplified in a very recent report showing that high-dose vitamin D supplementation during pregnancy improved bone health in children [4]. In this case, all participants were white and Danish.…”
Section: Vitamin D Basicsmentioning
confidence: 94%
“…Together with calcium, vitamin D helps protect This article is part of the Topical Collection on Photodermatology older adults from osteoporosis. There is strong, consistent evidence supporting the role of vitamin D in childhood bone health, although most studies have been done in a limited range of skin types, as exemplified in a very recent report showing that high-dose vitamin D supplementation during pregnancy improved bone health in children [4]. In this case, all participants were white and Danish.…”
Section: Vitamin D Basicsmentioning
confidence: 94%
“…Twelve RCTs [3,26,27,[30][31][32][33][34][35][36][37][38][39][40] involving a total of 4583 participants were included in this systematic review. Nine trials conducted vitamin D supplementation during pregnancy [3,26,27,30,31,33,34,36,40], and three trials performed vitamin D supplementation during infancy [30,34,38]. One study involved a subgroup of vitamin D supplementation in lactation [37].…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…One study [32] followed up children at 1 (Hazell 2014) [33] and 3 (Hazell 2017) [34] years of age. Six studies [3,26,[36][37][38][39] were placebo-controlled; four [27,30,34,40] were comparisons between higher vs. lower doses of vitamin D, and the lowest-dose group (400 IU/day) (this low dose is part of the standard care) served as the control; and two [33,36] involved control groups without supplements. All intervention groups were supplemented with cholecalciferol, except two studies [31,39] that used ergocalciferol supplementation.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…A review on the long-term effects of low maternal 25(OH)D levels on extra-skeletal health in offspring found some associations with disease, although evidence was conflicting and sparse [36]. However, a recent randomized trial showed effect of high dose vitamin D supplementation in the third trimester judged by improved bone mineralization in offspring up age six [37].…”
Section: Plos Onementioning
confidence: 99%